IMPLEMENTASI PROGRAM ILO (INTERNATIONAL LABOUR ORGANIZATION) DALAM MENGATASI PEKERJA ANAK DI INDONESIA TAHUN 2010 - 2014 - ", Nurmawinta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to explain how to implementation on programme ILO (International Labour Organization) in resolving the issue of child labour of defence in 2010 – 2014. Child labor is a problem that has long faced Indonesian, where children under the age of 18 are forced to work to meet the economic needs and various other factors. In this case, Child labour is children who are exploited to work with neither time nor even school and work in hazardous sectors for their safety. To face these issues, The Indonesian government has been cooperating with the ILO-IPEC. There are a lot of efforts have been made by the Indonesian government and the ILO, but child labour has always existed. In 2010-2014, the ILO has implemented the program on erasing Child Labour through Education.Data of this research was obtained from books, journals, articles, official documents and websites that support the hyphothesis. The author used Pluralism, and System and group level analyze. The theory used in this research concist of International Organizations by Tengku May Rudi.The result of this research shows that there is the implementation of the ILO program on overcoming Child Labor through Education in 2010 - 2014 runs well or in the sense of being implemented. This can be seen from the results or the number of child laborers who experienced a decline in 2015 after the implementation of the program for 4 years. Education is one of the interventions that are considered good enough in addressing the problem of child labor. but it is just a paradigm that grows in the community that works at an early age is good for future preparation. Therefore, awareness and understanding to the community about the child labours are really needed.Keywords: Child Labor, ILO - Indonesian, IPEC, Education